The determinants of entrepreneurship in developing countries - Calá, Carla Daniela (2015)
We address the question of what determines entrepreneurship in developing countries. In particular, because of the influence that this may have on the design of entrepreneurship policies, our main concern is whether the determinants of entrepreneurship are the same and/or have the same impact in developed and developing countries. To this end, we discuss the arguments put forward in the literature in support of the existence of differences in the determinants of entrepreneurship between developed and developing countries. We also analyse the results found in empirical studies on the determinants of formal firm entry (following the World Bank, our proxy of entrepreneurship) in developing countries and compare these results with those typically found in developed countries. Our main conclusion is that policy makers in developing economies should be careful when using evidence from developed countries to design entrepreneurship-promoting policies.